Socio-economic constraints in re-entering the labour market during COVID-19 and the resilience of female informal workers living in urban informal settlements - Nur, Jahid; Jabeen, Huraera (Taylor and Francis, 2024)
This article was published in The Asia Pacific Journal of Social Work and Development [©2023 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/02185385.2023.2195834 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/02185385.2023.2195834